Clinical pharmacist services within intensive care unit recovery clinics: An opinion of the critical care practice and research network of the American College of Clinical Pharmacy. Issue 7 (25th August 2020) - Mohammad, Rima A.; Betthauser, Kevin D.; Korona, Rebecca Bookstaver; Coe, Antoinette B.; Kolpek, Jimmi Hatton; Fritschle, Andrew C.; Jagow, Benjamin; Kenes, Michael; MacTavish, Pamela; Slampak‐Cindric, Angela A.; Whitten, Jessica A.; Jones, Carol; et al.
Abstract: Intensive care unit recovery clinics (ICU‐RCs) have been proposed as a potential mechanism to address the multifaceted unmet needs of intensive care unit (ICU) survivors and caregivers. The needs of this population include, but are not limited to, medication optimization, addressing physical function and psychological needs, coordination of care, and other interventions that may help in improving patient recovery and reducing the rate of preventable readmissions. The objective of this opinion paper is to identify and describe clinical pharmacy services for the management of ICU survivors and their caregivers in an ICU‐RC. The goals are to guide the establishment and development of clinical pharmacist involvement in ICU‐RCs and to highlight ICU recovery research and educational opportunities. Recommendations provided in this paper are based on the following: a review of published data on clinical pharmacist involvement in the ICU‐RCs; a consensus of clinical pharmacists who provide direct patient care to ICU survivors and caregivers; and a review of published guidelines and literature focusing on the management of ICU survivors and caregivers. These recommendations define areas of clinical pharmacist involvement in ICU‐RCs. Consequently, clinical pharmacists can promote education on Post Intensive Care Syndrome and Post Intensive Care Syndrome‐Family; improve medication adherence; facilitate appropriate referrals to primary care providers and specialists; ensure comprehensive medication management and medication reconciliation; provide assessment of inappropriate and appropriate medications after hospitalization; address adverse drug events, medication errors, and drug interactions; promote preventive measures; and facilitate medication acquisition with the goal of improving patient outcomes and reducing health care system costs.